Analysis of Semantics Learning Techniques in Understanding English Vocabulary in 6th Semester Students from University Muhammadiyah of Tangerang - Ayu Sintia, Desmi; Aidil Syah Putra; Aditia Hendri Maulana (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This study is the effectiveness of semantic learning techniques in understanding English vocabulary from the perspective of sixth semester students at Muhammadiyah University, Tangerang. This study used qualitative methods to collect data through interviews and classroom observations. The results showed that semantic learning techniques helped students in using polysemic materials to better understand the context and meaning of vocabulary, thus increasing their confidence in their daily use of English. This study also revealed some challenges faced by students and teachers when implementing semantic techniques in this sixth semester lesson. In this semantic learning technique, it is proven that students are more motivated to improve their vocabulary. It is hoped that in the future this research will be continued to help students better understand the semantic learning technique.